Achieving excellence in fundraising 4th edition - Sorensen, Chris 1976- (Gildan Audio, 2019)
Achieving Excellence in Fundraising is the go-to reference for fundraising principles, concepts, and techniques. With comprehensive guidance toward the fundraising role, this book reflects the latest advances in fundraising knowledge. Coverage includes evolving technologies, the importance of high net worth donors, global fundraising perspectives, results analysis and performance evaluation, accountability, and credentialing, with contributions from noted experts in the field. You'll gain essential insight into the practice of fundraising and the fundraising cycle. With contributions from members of The Fund Raising School and the faculty of Indiana University's Lilly Family School of Philanthropy, this new edition includes detailed guidance on nonprofit accounting practices as defined by the Financial Accounting Standards Board and the American Institute of Certified Public Accountants, rounding out the complete, thorough coverage of the fundraising profession. Designed to provide both theory and practical knowledge, this book is an all-in-one resource for anyone who performs fundraising duties.
Downloadable audio file
Keywords: BUSINESS & ECONOMICS; Nonprofit Organizations & Charities; General; Downloadable audio books; Audiobooks; Livres audio